On the Interval Selection and Interpretation of the Probabilistic AHP for Uncertain Decision Making - Shin, Minchul; Mo, Jeonghoon; Lee, Kyungsik; Lee, Cheol (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
We consider the uncertainty issue when multiple participants have dierent opinions on the importance of criteria in the Analytic Hierarchy Process (AHP). As the ranking can be reversed, robustness of ranking in the AHP is an important issue. In this work, we revisited the probabilistic AHP that utilizes Monte Carlo simulation of random pairwise comparison matrices and propose a new method in order to generate random ranges to avoid issues. We demonstrate the usefulness of the method through simulation. We also introduce an equivalence concept to better interpret the probabilistic output.